A Longitudinal Study of Adolescent Internet Addiction: The Role of Conscientiousness and Classroom Hostility. (July 2016) - Stavropoulos, Vasilis; Kuss, Daria; Griffiths, Mark; Motti-Stefanidi, Frosso
Over the last decade, research on Internet addiction (IA) has increased. However, almost all studies in the area are cross-sectional and do not examine the context in which Internet use takes place. Therefore, a longitudinal study examined the role of conscientiousness (as a personality trait) and classroom hostility (as a contextual factor) in the development of IA. The participants comprised 648 adolescents and were assessed over a 2-year period (while aged 16-18 years). A three-level hierarchical linear model was carried out on the data collected. Findings revealed that (a) lower conscientiousness was associated with IA and this did not change over time and (b) although being in a more hostile classroom did not initially have a significant effect, it increased girls' IA vulnerability over time and functioned protectively for boys. Results indicated that the contribution of individual and contextual IA factors may differ across genders and over time. More specifically, although the protective effect of conscientiousness appeared to hold, the over-time effect of classroom hostility increased the risk of IA for girls. These findings are discussed in relation to the psychological literature. The study's limitations and implications are also discussed.